2009
DOI: 10.1080/01488370903333538
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Forgiveness Process of Caregivers After the Death of Care-Receivers Diagnosed With Alzheimer's Disease

Abstract: This study explores the relationship of self-forgiveness and adaptive coping, religious/spiritual practices, social support, decreased grief, and mental well-being. 133 caregivers were surveyed. Bivariate analysis and stepwise regression models revealed that decreased grief, adaptive coping, and social support were significant in explaining the variation in self-forgiveness. This is one of the first studies to address self-forgiveness as part of the grieving process of Alzheimer's caregivers. Future directions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Under the studies conducted in literature, it is observed that self-forgiveness is related positively with self-respect [13], intellectual well-being [28], life satisfaction, positive feelings, cognitive flexibility [64], physical health [71] and empathy [23] but it is related negatively with anxiety and depression [64,65], anger, suicidality [24], and neurotic symptoms [20]. It is expected but also significant result that the concept of self-compassion is predicting the concept of self-forgiveness which has a positive relationship with many positive variables and a negative relationship with many negative variables in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Under the studies conducted in literature, it is observed that self-forgiveness is related positively with self-respect [13], intellectual well-being [28], life satisfaction, positive feelings, cognitive flexibility [64], physical health [71] and empathy [23] but it is related negatively with anxiety and depression [64,65], anger, suicidality [24], and neurotic symptoms [20]. It is expected but also significant result that the concept of self-compassion is predicting the concept of self-forgiveness which has a positive relationship with many positive variables and a negative relationship with many negative variables in literature.…”
Section: Discussionmentioning
confidence: 99%
“…The variables, cited by Jacinto (2007), included in this study are adaptive coping and non-adaptive coping. The variables will be defined here for the purpose of this study.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…This difficulty in communication has the potential to significantly increase the stress of caregiving and can tax the caregiver's coping resources. The care-receiver most likely will not be able to say good-bye to the caregiver, and this lack of closure can contribute to the caregiver experiencing an increase in feelings of guilt and regret (Jacinto, 2007). An important part of the process of resolving unfinished business with the care-receiver is self-forgiveness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations